The effects of neoliberalism on poverty in Egypt - Elmeligy, Adham Sameh (AUC Knowledge Fountain, 2018)
The issue of poverty is one of the major obstacles for economic and social development. Also, it is considered one of the key problems that negatively impact global economy. Egypt is one of the countries that suffered from poverty since 1960s. Poverty had widened the gap between the rich and poor. In 1990s, Egypt implemented neoliberal policies- namely structural readjustment and economic liberalization programs- for the sake of enhancing the economy and alleviating poverty. This thesis primarily examines the role of structural readjustment and economic liberalization programs in developing GDP and its negative impact on poverty reduction in Egypt. Furthermore, it discusses key economic policies and pro-poor policies adopted by different regimes in Egypt. The thesis concludes- as per the National Initiative to Develop the Poorest 1000 Villages - that the absence of good governance and rule of law led to the expansion rather than alleviation of poverty in Egypt.